Hedeoma salomeae (Lamiaceae), a new species from Nuevo León, Mexico - González-Gallegos, Jesús Guadalupe; Velázquez-Ríos, Perla; Martínez-Guerra, Marcelo Alí (Phytotaxa, 2025)
The American genus Hedeoma (Lamiaceae) concentrates its highest species richness in northern Mexico and the United States. It is one of Mexico’s most speciose Lamiaceae genera, and it is relatively well known based on recent taxonomic revisions, although it might require taxonomic rearrangements due to phylogenetic relationships. Northeastern Mexico has been previously identified as a center of diversity for the genus, primarily referring to isolated ravines at the foot of mountains or mountain tops and usually associated with limestone or gypsum patches. Routine examination of new observations of Mexican Lamiaceae in iNaturalist led to the discovery of a new Hedeoma species from the region mentioned above, supporting the observed distribution pattern of the genus. This new species is morphologically most similar to H. nana, which also grows in the same area. Still, it differs in the type of root system, density and compactness of the branching, stem indument, petiole length, calyx shape and symmetry, and corolla color. The new species is here described as H. salomeae, along with a diagnostic discussion against its most similar congener, botanical illustration, photographs, and a distribution map.